RETRACTED: RETRACTED: The Influence Of Product Quality, Promotion, And Lifestyle On Metro Department Store Pondok Indah Consumer Purchasing Decisions - Dhea Khoyrunnisa; elwisam elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
This study aims to analyze the Effect of Product Quality, Promotion, and Lifestyle, on the Purchasing Decisions of Metro Department Store Pondok Indah Mall Consumers. This study used primary data by distributing questionnaires as many as 100 respondents. Data analysis using Multiple Linear Regression analysis. The results of the study showed that the variables of Product Quality, Promotion, and Lifestyle had a positive and significant effect on Purchasing Decisions.